Serum Iron Levels Decreased in Patients with HBV-Related Hepatocellular Carcinoma, as a Risk Factor for the Prognosis of HBV-Related HCC - Wei, Yanyan; Ye, Wei; Zhao, Wei (Frontiers in Physiology, 2018)
Background: Hepatocellular carcinoma (HCC) is common and the second leading causes of cancer-related deaths. HCC usually occurs on the basis of chronic liver diseases. At present, the study of iron metabolism in chronic liver diseases was limited to chronic HCV infection, nonalcoholic fatty liver disease, and alcoholic liver disease. This study aimed to investigate the effect of serum iron levels on the progression of chronic HBV infection and the relationship with the prognosis of HBV-related HCC. Methods: A respective study involving 277 healthy individuals as controls (HC), 295 patients with chronic hepatitis B (CHB), 224 patients with HBV-related liver cirrhosis (HBV-related LC) and 586 patients with HBV- related HCC were enrolled in this study. Hematological parameters, HBVDNA and liver biochemistry were analyzed. Child-Pugh grade and BCLC stage of the HBV-related HCC patients were calculated. Results: The serum iron levels were lowest in the HBV- related HCC group as compared with HC, CHB and HBV-related LC groups (35.07±6.97, 27.37±10.26, 24.53±10.36 vs. 17.90±0.14, P<0.001). Strikingly, serum iron levels were lowest in HBV- related HCC patients with tumor size more than 10cm as compared with HBV- related HCC patients with tumor size smaller than 3cm, 3-5cm, and 5-10cm by subgroup analysis (22.12±0.94, 21.44±1.41, 15.65±0.98 vs. 13.36±1.15, P<0.001). Serum iron levels significantly decreased with worsening Child-Pugh grades and BCLC stages in HBV-related HCC group. In addition, serum iron levels was positively correlated with Retinol-Binding Protein, total bile acid, hemoglobin, and lymphocyte and negatively correlated with white blood cell and platelet in HBV- related HCC group. ROC curve analysis showed serum iron levels at 15.1umol/L as the optimal cut-off point for determining the survival of HBV-related HCC. By the Cox regression model analysis, serum iron levels less than 15.1umol/l together with higher AFP levels, worse BCLC stages, and larger tumor size showed higher mortality of HBV-related HCC patients (hazard ratio=2.280, 95% confidence interval, 1.815-2.865; P<0.001). Conclusions: Serum iron levels affected the progression of chronic HBV infection. The prognosis of HBV- related HCC patients with serum iron levels less than 15.1umol/l together with higher AFP levels, worse BCLC stages, and larger tumor lesion were poor.